PENGARUH SUBTITUSI TEPUNG BERAS HITAM TERHADAP KUALITAS COOKIES - Yolanda Intan Sari; Hendra Fauzi; Cici Andriani (Ensiklopedia of Journal, 2023)
This study aims to analyze the effect of substitution of black rice flour as much as 25%, 50% and 75% on the quality of cookies including the quality of shape, color, aroma, texture and taste. This research was carried out with pure experimental research using a completely randomized design method. The data used were primary data from 25 semi-trained panelists by filling in organoleptic questionnaires. The data were analyzed using ANAVA, a duncan test was performed if Fcount Ftable. The results showed a significant effect on the quality of color and taste, and there was no significant effect on the quality of shape, aroma, and texture. The best results based on organoleptic tests were found in X_1 with a 25% substitution of black rice flour.